Netherlands India A Study of Plural Economy - Furnivall, J. S. (Cambridge University Press, 1967)
A classic study of the subject and one of the major works in English on Dutch colonialism in Indonesia, Furnivall's magisterial history was published on the brink of the Second World War when Dutch power was waning in the archipelago. This study traces the economic and social development of Netherlands India from the arrival of the Dutch to 1939. It illustrates the geographical, economic and social features of the colony, and how Dutch and native Indonesian inhabitants co-existed within a unique, now lost, society and culture. Furnivall (1878–1960) served as a British colonial administrator in Burma for many years, and went on to become Professor of Burmese Studies at Cambridge University. The breadth and scope of this book make it an often cited and influential book in southeast Asian studies to this day
Title from publisher's bibliographic system (viewed on 05 Oct 2015)